2018
DOI: 10.1002/hep4.1185
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‐26‐5p functions as a new inhibitor of hepatoblastoma by repressing lin‐28 homolog B and aurora kinase a expression

Abstract: Hepatoblastoma (HB) is the most common liver tumor in children. Despite recent improvements in treatment strategies, the survival of children with hepatoblastoma remains poor. In this study, we identified a novel role of microRNA‐26a‐5p (miR‐26a‐5p), lin‐28 homolog B (LIN28B), Ras‐related nuclear protein (RAN), and aurora kinase A (AURKA) in HB. The expression of LIN28B, RAN, and AURKA was significantly up‐regulated in human HB livers and cell lines. Knockdown of LIN28B and RAN by small interfering RNAs inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Like in hepatoblastoma, AML and multiple myeloma, in this study, miR‐26a‐5p was also found downregulated in breast cancer, and low expression of miR‐26a‐5p predicted a negative index for the overall survival of breast cancer patients (Figure ). Overexpression of miR‐26a‐5p markedly inhibited breast cancer cell growth, and decreased the expression levels of cell cycle‐associated proteins (Figure ), which suggested that miR‐26a‐5p was a potential biomarker for breast cancer.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Like in hepatoblastoma, AML and multiple myeloma, in this study, miR‐26a‐5p was also found downregulated in breast cancer, and low expression of miR‐26a‐5p predicted a negative index for the overall survival of breast cancer patients (Figure ). Overexpression of miR‐26a‐5p markedly inhibited breast cancer cell growth, and decreased the expression levels of cell cycle‐associated proteins (Figure ), which suggested that miR‐26a‐5p was a potential biomarker for breast cancer.…”
Section: Discussionsupporting
confidence: 57%
“…MiR‐26a‐5p has been reported to be involved in the pathogenesis of several tumors. A recent paper reported that miR‐26a‐5p was a newly identified repressor of hepatoblastoma cell growth, and the decreased miR‐26a‐5p expression was correlated with the poor outcome of patients with hepatoblastoma . MiR‐26a‐5p targeted the 3′‐untranslated regions of LIN28B and AURKA, and markedly inhibited their expressions, along with suppressing hepatoblastoma cell growth and clonality .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zhang et al . showed in hepatoblastoma cells that miRNA‐26‐5p inhibited cell growth and proliferation by targeting LIN28B and aurora kinase A . In the present study, for the first time we showed that ALR induced proliferation through upregulation of miRNA‐26a, targeting the downregulation of PTEN, resulting in an enhanced p‐Akt/cyclin D1 pathway in hepatic cells.…”
Section: Introductionsupporting
confidence: 59%
“…It is noteworthy that two of the miRNAs (miR-125b and let-7a) in the cluster are LIN28B-related miRNA [27], indicating a potential molecular mechanism. Meanwhile, LIN28B and AURKA expressions were upregulated in a transcriptomic and genomic analysis of human hepatoblastoma, and miRNA-26-5p inhibited hepatoblastoma by repressing LIN28B [44]. LIN28B might also increase the risk of hepatoblastoma through LIN28B-RAN-AURKA pathway [44].…”
Section: Discussionmentioning
confidence: 98%